State Financial Control and Peculiarities of its Implementation in State Corporations - Viktoriya Vital’evna Romanovskaya (Учёт. Анализ. Аудит, 2019)
The control over the expenditure and the accumulation of budget funds by institutions with a significant share of state capital is an important aspect, since these institutions, on the one hand, receive financing from the budgets of the Russian Federation, and, on the other hand, bring public benefits and incomes in corresponding budgets of different levels. The article considers such categories as object and subject of control, types of control, as well as the standards and the specifics of carrying out control activities. The basis for the study was a more detailed examination and the analysis of the implementation of financial control in public corporations, which are a clear example of institutions with state capital shares. As a result, the following conclusions were drawn. First, the existing mechanism and system of control over the activities of state corporations are complex in coordination, but effective and contributing to the effectiveness and usefulness of the existence of these institutions. In addition, it was revealed that the rationally built system of internal control brings success in the functioning of state corporations.